Altered functional connectivity of interoception in illness anxiety disorder. (January 2017) - Grossi, Dario; Longarzo, Mariachiara; Quarantelli, Mario; Salvatore, Elena; Cavaliere, Carlo; De Luca, Paolofabrizio; Trojano, Luigi; Aiello, Marco
Abstract: Interoception collects all information coming from the body and is sustained by several brain areas such as insula and cingulate cortex. Here, we used resting-state functional magnetic resonance imaging to investigate functional connectivity (FC) of networks implied in interoception in patients with Illness anxiety disorders (IADs). We observed significantly reduced FC between the left extrastriate body area (EBA) and the paracentral lobule compared to healthy controls. Moreover, the correlation analysis between behavioural questionnaires and ROI to ROI FC showed that higher levels of illness anxiety were related to hyper-connectivity between EBA and amygdala and hippocampus. Scores on a questionnaire for interoceptive awareness were significantly correlated with higher FC between right hippocampus and nucleus accumbens bilaterally, and with higher connectivity between left anterior cingulate cortex (ACC) and left orbitofrontal cortex (OFC). Last, patients showed increased interoceptive awareness, measured by Self-Awareness Questionnaire (SAQ), and reduced capability in recognizing emotions, indicating inverse correlation between interoception and emotional awareness. Taken together our results suggested that, in absence of structural and micro-structural changes, patients with IADs show functional alteration in the neural network involved in the self-body representation; such functional alteration might be the target of possible treatments.